A study on lipoprotein(a) in health and type-2 diabetes mellitus - K. S., Premkumar (International Journal of Research in Medical Sciences, 2017)
Background: Increased lipoprotein (a) [Lp (a)] concentrations are predictive of coronary artery disease (CAD). Type 2 diabetes mellitus also leads to dyslipidemia, which are known risk factors for CAD. This study was designed to investigate the levels of Lp (a) in type 2 diabetic patients and their association with healthy controls and glycemic control. Methods: The study included 87 subjects out of which 20 were healthy volunteers. The remaining 67 were patients with type 2 diabetes from which 3 groups were formed 23 formed newly diagnosed group while those on treatment for diabetes were 44 out of which 22 were type 2 diabetics on oral hypoglycemic agents and the other 22 were type 2 diabetics on insulin. Individuals suffering from HT, renal disease, liver disease, thyroid dysfunction, nephrotic syndrome & cardiac disease, alcoholics, smokers or on lipid lowering drugs were excluded. Statistical analysis was done using the pearsons correlation. Results: Lp(a) levels were found to be significantly increased in the diabetic group irrespective of whether newly diagnosed not on treatment or old cases on treatment with oral hypoglycemic agents or insulin. Lp(a) levels showed no correlation to the degree of glycemic control in these patients. Lp(a) positively correlates with total cholesterol, LDLc and negatively with TGL and VLDLc in diabetics while it does not correlate with any of the lipid parameters in controls Conclusions: The results of the present study suggest that Lp(a) levels are increased in type 2 diabetic patients. The elevated Lp(a) levels do not reflect the glycemic status and correlates with increase in total cholesterol and LDLc suggesting similar metabolic pathways and the genetic connection for LDL and Lp(a).